Mt. Everest—we are going to lose many: a survey of fingerprint examiners' attitudes towards probabilistic reporting. (7th April 2021) - Swofford, H; Cole, S; King, V
Abstract: Over the past decade, with increasing scientific scrutiny on forensic reporting practices, there have been several efforts to introduce statistical thinking and probabilistic reasoning into forensic practice. These efforts have been met with mixed reactions—a common one being scepticism, or downright hostility, towards this objective. For probabilistic reasoning to be adopted in forensic practice, more than statistical knowledge will be necessary. Social scientific knowledge will be critical to effectively understand the sources of concern and barriers to implementation. This study reports the findings of a survey of forensic fingerprint examiners about reporting practices across the discipline and practitioners' attitudes and characterizations of probabilistic reporting. Overall, despite its adoption by a small number of practitioners, community-wide adoption of probabilistic reporting in the friction ridge discipline faces challenges. We found that almost no respondents currently report probabilistically. Perhaps more surprisingly, most respondents who claimed to report probabilistically, in fact, do not. Furthermore, we found that two-thirds of respondents perceive probabilistic reporting as 'inappropriate'—their most common concern being that defence attorneys would take advantage of uncertainty or that probabilistic reports would mislead, or be misunderstood by, other criminal justice system actors. If probabilistic reporting is to be adopted, much work is still needed to better educate practitioners on the importance and utility of probabilistic reasoning in order to facilitate a path towards improved reporting practices.